Extraction of essential oils from jasmine flower using solvent extraction based on petal condition - Muhammad Saifuddin, Idris (2008)
Pure Jasmine essential oils are primarily used in the perfumery industry and have a very high commercial value due to its therapeutic properties. As Jasmine essential oils are composed of heat-sensitive chemical compounds, the use of conventional steam distillation technique would inevitably inflict thermal degradation to the natural fragrance. In this experimental work, solvent extraction method using ethanol as solvent was employed due to its mild extracting condition and lower operating cost. Three different petal condition were used, which is dry petal,wet petal, and normal petal respectively. The extract compositions were compared using gas chromatography analysis. Preliminary results showed that volatile oil compounds were successfully isolated from Jasmine flowers using these conditions. It was found that the main constituents of the essential oils were benzyl acetate and benzyldehyde. Further studies also revealed that the composition and yield of essential oils was mainly influenced by the different types of petal condition used. The most optimum concentration which is Benzyl Benzoate Concentration 2.6370% and Benzaldehyde Concentration 1.0780% was extracted using dry petal condition . Low yield of the jasmine essential oils can be improved in future study by carrying out the research in larger scale.